PHYSICAL FITNESS OF PARATHLETES WITH SPINAL CORD INJURY OF TEAMS IN WHEELCHAIR BASKETBALL SANTA CATARINA. (Fiep Bulletin - online, 2011)
The rehabilitation of patients with spinal cord injury (SCI) is important for the development of functional independence and return to activities of daily living. The goal this research was to compare the physical fitness level from parathletes and sedentary groups with SCI that had and had not follow-up physiotherapy. The sample included 10 parathletes and 5 sedentary with SCI. The following measurements were performed: muscle strength and resistance in the prone rising trunk, sitting and rising, goniometry in flexion and extension of trunk, skinfolds of triceps, biceps, pectoral and abdomen, but also, blood pressure. The results showed that parathletes had the muscle strength and resistance, range of motion higher than sedentary control group (P
Keywords: spinal cord injury; physical fitness; physiotherapy